Evaluation of thermal, electrical and magnetic properties of NiMnSnGd shape memory alloys by changing Gd amount for keeping the tin ratio constant - Oner, Ecem; Kok, Mediha (Springer Heidelberg, 2021)
Heusler ferromagnetic shape memory alloys (FSMAs) have received significant attention due to their magnetocaloric effect. In this study, quaternary FSMAs based on NiMnSn alloyed with different amounts of Gd are investigated. The caloric, electrical and magnetic properties of the produced alloys are fully characterised. An increase in Gd alloying in the NiMnSn FSMAs results in a decrease in the characteristic temperatures. In addition, it is determined that the ratio of Mn and Ni is effective in changing the transformation temperature. The temperature-dependent electrical resistance measurements denote a sudden jump during the martensite phase transformation, while a decrease in the resistance value is observed during the austenite phase transformation. According to the magnetisation hysteresis, Gd significantly increases the magnetisation of the NiMnSn-based alloy.
Keywords: Twin-Boundary Motion; Mechanical-Properties; Martensitic-Transformation; Phase-Transitions; Crystal-Structure; Microstructure; Temperatures; Behaviors; Boron